Nutritional Counseling for Head and Neck Cancer Patients Undergoing (Chemo) Radiotherapy—A Prospective Randomized Trial - Orell, Helena; Schwab, Ursula; Saarilahti, Kauko; Österlund, Pia; Ravasco, Paula; Mäkitie, Antti (Frontiers in Nutrition, 2019)
Background: Head and neck cancer and its treatment may deteriorate nutrition status. Previous data have shown that intensive nutrition intervention by a dietician reduces radiation-induced adverse events including weight loss. Objective: To determine if on-demand nutrition counselling (ODC) would be as effective as intensive nutrition counselling (INC) in patients undergoing (chemo)radiotherapy. Methods: Fifty-eight patients were randomly assigned to receive INC (n=26) or ODC (n=32). Outcome measures were nutrition status (PG-SGA), weight loss, handgrip strength (HGS), body composition and survival. Results: Weight loss and impaired nutrition parameters during oncological treatment were seen equally in both groups (NS). Leaner patients at baseline maintained their weight, while overweight patients lost both weight and handgrip strength during treatment. Disease- free survival (DFS) (median=43 months) was not affected by weight loss during treatment. Lower baseline HGS and malnutrition were associated with worse DFS (low vs. normal HGS: 15 vs. 42 months; p=0.05 and malnutrition vs. good nutrition status: 17 vs. 42 months; p=0.014, respectively). Survival according to low vs. normal HGS in the INC group was 4 vs. 44 months (p=0.007) and in the ODC group 28 vs. 40 months (p=0.944). According to malnutrition vs. good nutrition status in the INC group, DFS was 21 vs. 43 months (p=0.025) and in the ODC group 15 vs. 41 months (p=0.03). Conclusions: Individualised on-demand nutrition counselling was as efficient as intensive counselling during (chemo)radiotherapy. Overweight patients had more severe weight loss but not poorer survival. Low HGS and malnutrition at baseline were directly associated with poor survival.